Quasi-static characterisation of asphalt mixtures - Dunhill, Stuart Thomas (2002)
A modern road pavement is a highly complex structure. Paving materials can exhibit non-linear and time dependent material properties whilst subjected to complicated three-dimensional loading conditions that are functions of the specific construction of each pavement. Nevertheless, empirical or linear elastic techniques, which cannot fully describe such factors, are often used in road engineering to assess pavement deterioration. An alternative approach is the use of finite element techniques, incorporating more complex constitutive models, to describe the response of asphalts and other paving materials.